A Sociological View on Marital Satisfaction: Measuring Capabilities - Олеся Золотнюк (Социологическое обозрение, 2014)
This article is devoted to demonstrating the capabilities of sociology in the measuring of certain aspects of family life. The study of different aspects of human activity has always been the subject of heated debates across various sciences. Sociology is not an exception. Most often, social scientists study human activity in order to predict social behavior and to build models of these processes. Also, the development of incentive programs which stimulate the growth or the decline of certain indicators in a proper manner has gained popularity in recent times. In the spotlight of this article is mating behavior as one form of human activity, using the concept of marital satisfaction as an empirical referent. The author considers marital satisfaction as a fundamental component of the family-complex study, and proposes to examine the basic sociological methods that are used to investigate this area. For a better understanding of mating behavior, the author touches upon the problems of attitude-measuring in the use of Likert scale, demonstrates ideas of the R.Udry sociological test, describesthe Whitfield’s R. «altruistic pyramid», illustratesthe scale of love and sympathy, developed by Zeke Rubin, and the Soviet researchers of family as a social institution are also mentioned in this article. Scientific and technological progress also helps in the development of measurement techniques. This kind of measuring procedure is also represented in this article. The idea of ​​developing Data Mining is positioned by the author as a major step in the development of analysis without subjectivity. The conclusion to this article highlights the importance of using multiple methods for a representative study.